2013
DOI: 10.1186/1297-9716-44-31
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, molecular virology and diagnostics of Schmallenberg virus, an emerging orthobunyavirus in Europe

Abstract: After the unexpected emergence of Bluetongue virus serotype 8 (BTV-8) in northern Europe in 2006, another arbovirus, Schmallenberg virus (SBV), emerged in Europe in 2011 causing a new economically important disease in ruminants. The virus, belonging to the Orthobunyavirus genus in the Bunyaviridae family, was first detected in Germany, in The Netherlands and in Belgium in 2011 and soon after in the United Kingdom, France, Italy, Luxembourg, Spain, Denmark and Switzerland. This review describes the current know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 94 publications
0
79
0
7
Order By: Relevance
“…Hyperthermia and drop in milk production were reported in adult dairy cows in north-west Germany and the Netherlands, and in some cases, transient diarrhoea was also recorded in the Netherlands [2]. Farmers and veterinarians in North Rhine-Westphalia, Germany, and in the Netherlands reported an unidentified disease in dairy cattle with a short period of clear clinical signs to the animal health services, local diagnostic laboratories and national research institutes [1].…”
Section: The Origin Of Schmallenberg Virusmentioning
confidence: 99%
“…Hyperthermia and drop in milk production were reported in adult dairy cows in north-west Germany and the Netherlands, and in some cases, transient diarrhoea was also recorded in the Netherlands [2]. Farmers and veterinarians in North Rhine-Westphalia, Germany, and in the Netherlands reported an unidentified disease in dairy cattle with a short period of clear clinical signs to the animal health services, local diagnostic laboratories and national research institutes [1].…”
Section: The Origin Of Schmallenberg Virusmentioning
confidence: 99%
“…The acute disease in pregnant females was followed by an epidemic of stillbirths and congenital malformations, suggesting an infection in the uterus that affects the fetus in the different stages of the gestational process. In sheep and goats, this virus causes congenital malformations in the fetuses of infected females (Doceul et al 2013). Several studies have demonstrated that natural or experimentally induced antibodies can survive for over a year in ruminants, and this humoral immunity protects the animal against clinical signs, RNAemia and virus replication in target organs upon reinfection for at least 15 months (Poskin et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The acute disease in pregnant females was followed by an epidemic of stillbirths and congenital malformations, suggesting an infection in the uterus that affects the fetus in the different stages of the gestational process. In sheep and goats, this virus causes congenital malformations in the fetuses of infected females (Doceul et al 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous parts of the world, there have been several recent reports of disease outbreaks associated with insecttransmitted viruses, or arboviruses (Doceul et al, 2013;MacLachlan & Guthrie, 2010;Weaver & Reisen, 2010). The 2006 outbreak of a 'bluetongue-like' disease in Israeli dairy herds is an example that also had significant economic consequences on the dairy industry (Kedmi et al, 2010b;Yadin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%